The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fmed.2022.1024762
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ciprofol for agitation and delirium in the ICU: A multicenter, single-blind, 3-arm parallel randomized controlled trial study protocol

Abstract: BackgroundAgitation is very common in the intensive care unit (ICU). The causes include pain, delirium, underlying disease, withdrawal syndrome, and some drug treatments. The practical goal of ICU treatment is to find an appropriate sedation regimen to reduce pain, restlessness, and delirium. Previous trials have examined the use of dexmedetomidine, but no trials have evaluated the efficacy and safety of ciprofol, a new sedative drug.MethodsThis study was a multicenter, single-blind, 3-arm parallel randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Some have highlighted the safety and effectiveness of ciprofol in anesthesia induction, with a lower incidence of adverse events [ 26 ]. In contrast, others have noted that propofol remains a standard and safe choice for anesthesia induction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some have highlighted the safety and effectiveness of ciprofol in anesthesia induction, with a lower incidence of adverse events [ 26 ]. In contrast, others have noted that propofol remains a standard and safe choice for anesthesia induction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the effectiveness and safety of ciprofol have been recognized [22][23][24], however, due to its short marketing time, there is no reference dose for the use of ciprofol in special populations with low immunity such as TB. Therefore, this study prospectively included TB patients and calculated the ED50 of ciprofol combined with 0.15 µg/kg sufentanil for beroptic bronchoscopy examination of non-elderly men, nonelderly women, elderly men, and elderly women with TB by sequential test method, in order to provide a reliable basis for the effectiveness of ciprofol.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that ciprofol has a shorter half-life than dexmedetomidine and has demonstrated promising sedation and delirium control outcomes in ICU patients. It is anticipated to exhibit comparable efficacy to propofol while presenting fewer complications in ICU patients [ 41 , 42 ]. Both dexmedetomidine and ciprofol have served as focal points in clinical trials evaluating their efficacy and safety in sedation and anesthesia, each displaying potential advantages in various clinical scenarios.…”
Section: Reviewmentioning
confidence: 99%